2019
DOI: 10.1039/c8dt04877k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structure and DFT calculations of 1,2-N-substituted o-carboranes

Abstract: A series of 1,2-N-substituted o-carboranes were obtained. Ultra-long C–C distances were found in the secondary-amino o-carboranes 3. The relationship between C–C bond lengths and the electron effects of the benzyl groups was discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…[50][51][52] There have been theoretical studies of the electronic and steric effects of exohedral substituents on this C-C bond length. 53,54 The electronic interaction between exohedral donor groups and the carborane cluster can be very significant, as evidenced by the recently disclosed structure of the diamine derivative 1,2-(MesCH 2 NH) 2 -C 2 B 10 H 10 , which features one of the longest reported C-C bonds (1.931(3) Å, cf. 1.624(8) Å for the parent unsubstituted cluster).…”
Section: Bryce C Nussbaummentioning
confidence: 99%
“…[50][51][52] There have been theoretical studies of the electronic and steric effects of exohedral substituents on this C-C bond length. 53,54 The electronic interaction between exohedral donor groups and the carborane cluster can be very significant, as evidenced by the recently disclosed structure of the diamine derivative 1,2-(MesCH 2 NH) 2 -C 2 B 10 H 10 , which features one of the longest reported C-C bonds (1.931(3) Å, cf. 1.624(8) Å for the parent unsubstituted cluster).…”
Section: Bryce C Nussbaummentioning
confidence: 99%
“…Surprisingly, 1-NCO- o -carborane has a reported ν NCO value of 2258 cm –1 : on the basis of inductive effects, it would be expected that the stretching frequency would be even higher than that of the B(3) derivative. However, Teixidor and others have previously suggested that C-bound substituents with available lone pairs can donate electron density back into the cage with concomitant C–C bond lengthening, which may in part explain the deviation in this trend. Unfortunately, at this point we are unable to compare this observation with the analogous azide system.…”
Section: Resultsmentioning
confidence: 95%
“…We have reported the facile synthesis and functionalization of diamino o -carborane (Chart ). These secondary amino o -carboranes were used as supporting ligands for N -heterocyclic carbenes and the carbene complexes . We envisioned the diamino o -carborane could also be used to synthesize salen-type ligands and metal–salen complexes (Chart ).…”
Section: Introductionmentioning
confidence: 99%